1976
DOI: 10.1073/pnas.73.6.2123
|View full text |Cite
|
Sign up to set email alerts
|

Immunological cross-reactivity of antibodies to a synthetic undecapeptide analogous to the amino terminal segment of carcinoembryonic antigen, with the intact protein and with human sera.

Abstract: A peptide corresponding to the 11 amino acid residues of the NHT-terminal portion in the sequence of carcinoembryonic antigen(CEA) has been synthesized by the solid phase technique. The synthetic CEA(1-11) peptide was attached by means of a water-soluble carbodiimide reagent to multichain poly(DL-alanine) as well as to bovine serum albumin. Both macromolecular conjugates provoked in rabbit anti-CEA(1-11) peptide antibodies. The specificity of this immunological system and the crossreactivity between the peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 30 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…For example, antibodies provoked by a synthetic peptide comprising the "loop" region of the enzyme lysozyme attached to a synthetic carrier were reactive with native lysozyme (5). Similarly, antibodies elicited by a synthetic antigen containing the NH2-terminal region of the carcinoembryonic antigen of the colon were reactive with the intact protein, and capable of detecting carcinoembryonic antigens in sera of cancer patients (6). We have also shown that this approach could be used for provoking an antiviral response.…”
mentioning
confidence: 85%
“…For example, antibodies provoked by a synthetic peptide comprising the "loop" region of the enzyme lysozyme attached to a synthetic carrier were reactive with native lysozyme (5). Similarly, antibodies elicited by a synthetic antigen containing the NH2-terminal region of the carcinoembryonic antigen of the colon were reactive with the intact protein, and capable of detecting carcinoembryonic antigens in sera of cancer patients (6). We have also shown that this approach could be used for provoking an antiviral response.…”
mentioning
confidence: 85%
“…We first synthesized a peptide from the amino terminus of the carcinoembryonic antigen of the colon; this showed a weak cross-reaction with the intact antigen (55). The first study related to viruses was the synthesis of a peptide from the envelope of the MS2 bacteriophage (34).…”
Section: Synthetic Vaccinesmentioning
confidence: 99%